2019
DOI: 10.1002/iub.2153
|View full text |Cite
|
Sign up to set email alerts
|

Role of a novel circulatory RNA‐based biomarker panel expression in ovarian cancer

Abstract: Ovarian cancer (OC) is considered the sixth commonest cancer affecting women globally. We choose novel integrated specific ovarian cancer RNA biomarker panel; pellino E3 ubiquitin protein ligase family member 3 (PELI3) gene expressions along with its selected epigenetic regulators (microRNA (miR-361-3p) and long noncoding RNA (lncRNA RP5-837J1.2) by bioinformatic methods. Then, differential expressions of the selected panel in the sera of 50 OC patients, 42 cases with benign ovarian lesions, and among 45 contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Even though CA125 protein is currently the standard diagnostic marker for ovarian cancer, only one third of the studies directly compare the performance of (combinations of) RNA markers to CA125. Individual levels of serum EV miR-145 [15], serum EV miR-200b [15], plasma circBNC2, and serum RPS-8337J1.2 [25] resulted in a higher AUC than that of the CA125 protein. The combination of miR-205 and let-7f was also able to outperform CA125 [42], just like a neural network based on 14 miRNAs [46].…”
Section: Diagnostic Performance Of the Reported Modelsmentioning
confidence: 88%
See 2 more Smart Citations
“…Even though CA125 protein is currently the standard diagnostic marker for ovarian cancer, only one third of the studies directly compare the performance of (combinations of) RNA markers to CA125. Individual levels of serum EV miR-145 [15], serum EV miR-200b [15], plasma circBNC2, and serum RPS-8337J1.2 [25] resulted in a higher AUC than that of the CA125 protein. The combination of miR-205 and let-7f was also able to outperform CA125 [42], just like a neural network based on 14 miRNAs [46].…”
Section: Diagnostic Performance Of the Reported Modelsmentioning
confidence: 88%
“…Although the extracellular transcriptome of human biofluids is complex and diverse, most liquid biopsy studies in this field focused on miRNAs (30/36). Only two studies looked into circRNAs [23,27], two studies investigated mRNAs [18,38], one study looked into long noncoding RNAs (lncRNAs) [45] and one study looked into a combination of one miRNA, one lncRNA and one mRNA [25]. Surprisingly, RNA sequencing for unbiased biomarker discovery is rarely used in the reported literature on RNA biomarkers for early diagnosis of ovarian cancer.…”
Section: Basic Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum samples were collected from clinical patients with OC, those with benign ovarian disease, and controls. Then, the differential gene expression levels in the serum were detected using RT–PCR methods ( 46 ). The results showed that serum lncRNA RP5 expression was significantly upregulated in the malignant tumor group compared with the benign and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA RP5 expression was lower in malignant ovarian tissue and adjacent nontumor tissues from patients with OC than in normal tissues. Furthermore, the operator characteristic curves showed that the expression values of lncRNA RP5 obviously distinguished the patients with OC from patients with benign masses and control patients, with an accuracy rate of 96% ( 46 ). These results indicate that these new diagnostic biomarker RNAs could help diagnose OC and could be of great importance for the early detection and treatment of clinical tumors.…”
Section: Discussionmentioning
confidence: 99%